2019
DOI: 10.3390/nano9010066
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterization of AlGaN-Based UV LEDs with a ITO/Ga2O3/Ag/Ga2O3 Transparent Conductive Electrode

Abstract: We fabricated a complex transparent conductive electrode (TCE) based on Ga2O3 for AlGaN-based ultraviolet light-emitting diodes. The complex TCE consists of a 10 nm ITO, a 15 nm Ga2O3, a 7 nm Ag, and a 15 nm Ga2O3, forming a ITO/Ga2O3/Ag/Ga2O3 multilayer. The metal layer embedded into Ga2O3 and the thin ITO contact layer improves current spreading and electrode contact properties. It is found that the ITO/Ga2O3/Ag/Ga2O3 multilayer can reach a 92.8% transmittance at 365 nm and a specific contact resistance of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…In a previous study, we demonstrated that the ITO/Ga 2 O 3 /Ag/Ga 2 O 3 multilayer has advantages in conductivity and transmittance for UV LEDs compared to ITO [27]. The ITO/Ga 2 O 3 /Ag/Ga 2 O 3 multilayer consists of an ITO contact layer, a Ga 2 O 3 layer, an Ag metal layer, and another Ga 2 O 3 layer, which are deposited in sequence.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, we demonstrated that the ITO/Ga 2 O 3 /Ag/Ga 2 O 3 multilayer has advantages in conductivity and transmittance for UV LEDs compared to ITO [27]. The ITO/Ga 2 O 3 /Ag/Ga 2 O 3 multilayer consists of an ITO contact layer, a Ga 2 O 3 layer, an Ag metal layer, and another Ga 2 O 3 layer, which are deposited in sequence.…”
Section: Introductionmentioning
confidence: 99%
“…Ga 2 O 3 is a wide-bandgap semiconductor with ~4.9 eV; it is an optically transparent material and features poor conductivity [7]. Therefore, Ga 2 O 3 is the most commonly used component in electronic devices, such as ultraviolet (UV) photodetectors, power electronic devices, light-emitting diodes, and transparent conducting films [8,9,10,11]. However, Ga is a carrier suppressor, which reduces oxygen vacancy in control carrier concentrations in multicomponent oxide TFT devices.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the effect of oxygen-doped sputtered AlN NL on the subsequent AlN film is important to the realization of high-efficiency DUV LEDs. On the other hand, the crystalline structure of AlN film is closely related with the thickness of sputtered AlN NL [30,31,32,33,34]. The characteristics of AlN film on sapphire substrate with different thicknesses of sputtered AlN NL is of significant interest for DUV LEDs.…”
Section: Introductionmentioning
confidence: 99%